STRUCTURAL-FUNCTIONAL ASPECTS IN THE EVOLUTION OF OPERCULATE CORALS (RUGOSA) - Gudo M. (My University, 2002)
Among the Rugosa operculae were developed by only a few genera. One is the slipper-shaped Calceola and another is the pyramidal shaped Goniophyllum. On the basis of biological and morphological knowledge of recent corals, the two different bauplans of the soft bodies of Calceola and Goniophyllum have been reconstructed. The soft body (i.e. the polyp) of a rugose coral is thought to have all the basic structures of anthozoan polyps: a barrel-like body shape, a flat oral disc with tentacles, and a mouth from which a pharynx reaches inside the gastric cavity. Furthermore, as in all Anthozoa, Rugosa had internal mesenteries that act as tensile cords; during growth in the diameter further mesenteries were inserted. In contrast to all other Anthozoa, in the Rugosa new single mesenteries were added in four insertion sectors. The bauplans of Calceola and Goniophyllum differ in the pattern of mesentery insertion into these four sectors. Calceola had a serial insertion pattern and Goniophyllum had a symmetrical insertion pattern. They are representatives of the two different bauplans within the Rugosa. The lid corals are examples of convergent evolved genera; Calceola as well as Goniophyllum originated by quite simple modifications of the ancestral type. The peculiar shapes, the operculae and especially the straight hinges between the calyx and the lid(s) result only from mechanical necessity. Under special conditions (such as high sedimentation rates) these modifications of the corallites represent suitable tactics for survival.
Keywords: RUGOSA; CALCEOLA; GONIOPHYLLUM; ENGINEERING MORPHOLOGY; SOFT BODY RECONSTRUCTION